ISLAMIC COPING MECHANISM DALAM MENGATASI BURNOUT: TELAAH SURAT AL-INSYIRAH PERSPEKTIF TAFSIR FI ZHILAL AL-QUR’AN - Kilau Aurum Auliya; Yeti Dahliana (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Burnout is a condition of physical, emotional, and mental exhaustion due to prolonged stress, which is common in students and workers. One relevant approach to overcome it is the Islamic coping mechanism, which is a psychological recovery strategy based on Islamic spiritual values. This study aims to examine the form of Islamic coping mechanism in dealing with burnout based on the interpretation of Surah Al-Insyirah in the perspective of the interpretation of Fī Ẓilal Al-Qur'an by Sayyid Qutb. This study uses a qualitative method with a psychological approach through literature study. The analysis focuses on verses in Surah Al-Insyirah that are relevant to the Solution to handling burnout. The results of the study concluded three main strategies offered by the Qur'an: (1) believing that every difficulty is accompanied by ease (QS. Al-Insyirah: 5-6), (2) continuing activities after completing tasks (QS. Al-Insyirah: 7), and (3) surrendering completely to Allah as a source of inner peace (QS. Al-Insyirah: 8). This shows that Surah Al-Insyirah contains spiritual coping values that can act as a recovery mechanism against burnout as a whole, especially in the context of modern life that is full of stress.